A New Approach For Text Detection In Natural Scene Images (International Journal of Engineering and Computer Science, 2015)
Text detection in natural scene pictures is a very important requirement for several content-based image analysis tasks. Text data facilitate to perceive a picture, scanned document analysis, electricity meters, reading of street name, automobile vehicle plate reading, detection and translation of sign, mobile text characters recognition by image processing. This paper tend to propose associate correct and study methodology for police investigation texts in natural scene pictures. a quick and effective pruning algorithmic program is intended to extract Maximally Stable Extremal Regions (MSERs) as character candidates exploitation the strategy of minimizing regular variations. Character candidates square measure classified into text candidates by the single-link bunch algorithmic program which is used here, wherever distance weights and bunch threshold square measure learned mechanically by a unique self-training distance metric learning algorithmic program.